Peroxisome proliferator-activated receptors (PPARs) in health and disease. - Ehrmann, Jiří; Vavrušová, Nicol; Collan, Yrjo; Kolář, Zdeněk (Biomedical papers, 2002)
Peroxisome proliferator-activated receptors (PPARs) belong to the superfamily of steroid-thyroid-retinoid nuclear receptors. PPARs are transcription factors activated by specific ligands and play an important role during cell signalling. Intensive study of PPARs during recent years has revealed their importance in both normal physiology and in the pathology of various tissues. They participate in the regulation of lipid metabolism, inflammation and the development of atherosclerosis or diabetes. They also play a role in the regulation of growth and differentiation of cancer. It has been suggested that PPAR ligands may have potent anticancer effects and thereFirst may serve as potential anticancer drugs. In this review we focus on a role of PPARs in breast cancer and in glial tumors of the brain.
Keywords: Orphan receptors / PPARs / Inflammation / Atherosclerosis / Cancer